Floristic composition and structure of the gallery forest of Parque Vapor Cué, Paraguay - Díaz Lezcano, Maura I. (2023)
Gallery forests are characteristic plant communities on the banks of rivers and streams, which provide important ecosystem services. The goal of this research was to analyze the floristic composition and structure of the gallery forest in the Vapor Cué Park, located in the Paraguay Central ecoregion, in the Department of Cordillera, Paraguay. Five plots of 750 m² (25 m × 30 m) were installed and the floristic composition of the tree species and the different parameters of the horizontal (abundance, frequency, dominance, and importance value index) and vertical (sociological position) structure were determined. absolute and relative), in addition to the diametric structure. A total of 112 individuals with DAP ≥ 10 cm were recorded, corresponding to 8 genera and 8 species [Celtis pubescens Spreng., Rheedia brasiliensis (Mart.) Planch. & Triana, Croton urucurana Baill., Peltophorum dubium (Spreng.) Taub., Inga marginata Wild., Eugenia uniflora L., Citrus × limon (L.) Osbeck, Chrysophyllum gonocarpum (Mart. & Eichler ex Miq.) Engl.] and 7 families (Cannabaceae, Clusiaceae, Euphorbiaceae, Fabaceae, Myrtaceae, Rutaceae, Sapotaceae). The species with the highest abundance, frequency, dominance, and importance value index was Inga marginata. The mixing ratio presented a value of 6.25. The calculated phytosociological value indicated that 29 % of the species were in the lower stratum, 50 % in the middle stratum and 21 %. at the top. The gallery forest of the Vapor Cué Park has a structure characterized by native forest species, the most ecologically important being Inga marginata and considering the phytosociological value, it is concluded that the middle stratum is the dominant one.